PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWER POINT BAGI GURU-GURU DI SMA AL-FALAH HMM TIMIKA - A. Rasul; Subhanudin Subhanudin; Habibi Sutirta (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The purpose of this service activity is to provide training and knowledge to teachers who teach at SMA Al-Falah HMM Timika about making power point-based learning media that are useful as teaching materials to make it easier for teachers to explain or explain various learning materials to be taught. The steps taken by the team in carrying out this activity are as follows: (1) Action planning, (2) Action Implementation, (3) Observation/Evaluation, and (4) Reflection. The existence of learning media will make it easier for teachers to explain various materials in learning